Association between neutrophil-to-lymphocyte ratio and left ventricular diastolic dysfunction in patients with type 2 diabetes mellitus - Yang, Xueyang; Shi, Yinze; Zhang, Huan; Huang, Liying; Zhang, Jiaoyue; Min, Jie; Chen, Lulu (Frontiers in Endocrinology, 2025)
BackgroundDiabetes has become a global pandemic, posing a sustained threat to human health, primarily due to its associated complications. Left ventricular diastolic dysfunction (LVDD) is a prevalent cardiac complication among patients with diabetes. Since most patients are asymptomatic and lack relevant biomarkers, LVDD has not attracted significant attention from clinicians. The neutrophil-to-lymphocyte ratio (NLR) is a widely studied inflammation biomarker that has been suggested to be linked to various medical conditions, including cardiac diseases. However, its association with LVDD among patients with type 2 diabetes mellitus (T2DM) has not been explored.AimTo clarify the relationship between NLR and LVDD among patients with type 2 diabetes.MethodsWe conducted a cross-sectional study using medical records from 855 patients diagnosed with T2DM who were admitted to the Endocrinology department at Wuhan Union Hospital. According to the ASE/EACVI 2016 recommendations, these patients were categorized into two groups based on sonographic parameters: patients with normal left ventricular diastolic function (the non-LVDD group) and patients with LVDD (the LVDD group). NLR values were calculated and divided into three different levels. Statistical analysis was conducted to evaluate the correlation between NLR levels and the prevalence of LVDD.ResultsThe prevalence of LVDD among hospitalized patients with T2DM in our study was 47.8% (409/855). The mean NLR value of the LVDD group was significantly higher compared with the non-LVDD group [1.60 (1.24-2.05) vs 1.85 (1.44-2.31), P<0.001]. The prevalence of LVDD in the three different NLR levels was 35.51% (76/214), 49.27% (203/412), and 56.77% (130/229), respectively. Unjustified logistic analysis showed that NLR levels were positively associated with the prevalence of LVDD (P <0.001). Compared to the low level of NLR, the unadjusted odds ratios (OR) of LVDD at the medium and high levels were 1.764 (1.255-2.478, P=0.001) and 2.384 (1.626-3.497, P<0.001), respectively (P for trend <0.001).ConclusionOur findings suggest that the NLR is a potential indicator for assisting clinicians in identifying LVDD in patients with T2DM. Patients with elevated NLR levels may be at a greater risk of developing LVDD than those with lower NLR levels, which may require attention and interventions to prevent patients from progressing into heart failure.